Reserve Estimation Using Decline Curve Analysis for Block 74F-S Oil Field (Comprehensive Journal of Science, 2025)
This study employs DCA to estimate the remaining reserves of the SABAH oil field within concession 74F-S by using the Oil Field Manager (OFM) software 2019 version; provided by SENSIA-SLB. Specifically, our estimated reserves using OFM software predicted to be 26.069 (MMbbl) with (ARE %) equal to 0.27%, The obtained results for these wells reported as in following:Well 18/74F-S–remaining reserve estimation=2.274 MMbbl. Well 20/74F-S – remaining reserve estimation=2.171MMbbl. Well 31/74F-S – remaining reserve estimation = 0.270 MMbbl. Well 37/74F-S–remaining reserve estimation=0.074 MMbbl.Also, ARPS recovery factor’s correlation resulted a lower (ARE % = 2.23%) among the correlations used to calculate (RF); when compared to the (RF) provided by Zueitina Co. “49.31%”.
Keywords: Decline Curve Analysis (DCA); Remaining Oil Reserves; Oil Field Manager (OFM); ARPS Model; Recovery Factor; Reservoir Performance; SABAH Oil Field